Evaluation of the mTORC activity in the presence of Toxoplasma gondii and azathioprine in human monocyte cell line - Sara Nemati; Hanieh Mohammad Rahimi; Anna Meyfour; Hossein Pazoki; Hamid Asadzadeh Aghdaei; Shabnam Shahrokh; Hamed Mirjalali (BMC Microbiology, 2023)
Abstract Background Autophagy is an important part of pathogenesis of IBD. Thiopurines such as azathioprine (AZA) are approved drugs for clinical practices in IBD patients. Besides, as an escape strategy, Toxoplasma gondii can use the mTORC1 complex to inactivate autophagy. Methods In this study, we investigated whether T. gondii tachyzoites may modulate autophagy and interfere the effects of azathioprine in IBD treatment. PMA-activated human monocyte cell line (THP-1) was infected with fresh T. gondii RH tachyzoites. After 5 h of infection, the cells were treated with AZA for 6 h. The expression of atg5, atg7, atg12, lc3b, and β-actin (BACT) genes was evaluated using quantitative real-time PCR. To analyze the phosphorylation of ribosomal protein S6 (rpS6), western blot using specific primary antibodies was performed. Results The results of real-time PCR revealed that AZA, T. gondii tachyzoites, and a combination of AZA and T. gondii tachyzoites upregulated atg5 gene for 4.297-fold (P-value = 0.014), 2.49-fold (P-value = 0.006), and 4.76-fold (P-value = 0.001), respectively. The atg7 gene showed significant upregulation (2.272-fold; P-value = 0.014) and (1.51-fold; P-value = 0.020) in AZA and AZA / T. gondii, respectively. The expression of atg12 gene was significantly downregulated in AZA and T. gondii tachyzoites for (8.85-fold; P-value = 0.004) and (2.005-fold; P-value = 0.038), respectively, but upregulated in T. gondii/AZA (1.52-fold; P-value = 0.037). In addition, the lc3b gene was only significantly changed in AZA / T. gondii (3.028-fold; P-value = 0.001). Western blot analysis showed that T. gondii tachyzoites significantly phosphorylated rpS6, and tachyzoites did not interfere the effects of AZA to phosphorylate the rpS6. Conclusion Taken together, although AZA and T. gondii similarly affects the expression levels of atg5, atg7, and atg12, but T. gondii does not seem to modulate the effects of AZA via mTORC functions.